Why the risk-adjusted discount rate method is a better method than the certainty equivalent method: a teaching perspective. (2017) - Nippani, Srinivas
One of the more popular methods of risk analysis in capital budgeting is the certainty equivalent method. In this paper, we discuss the major drawbacks of using this method, and strongly argue in favour of the risk-adjusted discount rate method. The calculation of certainty equivalent factors, the use of risk-free rate as the discount rate, the reinvestment rate assumption and the practical problems for multinational corporations for using the certainty equivalent method are discussed. We also discuss the concept of cost of capital and its role in relation to the use of the two methods of risk analysis.